The AO Ulnar Shortening Osteotomy System Indications and Surgical Technique - Nagy, Ladislav; Jungwirth-Weinberger, Anna; Campbell, Douglas; Pino, Juan González del (Journal of Wrist Surgery, 2014)
Ulnar shortening osteotomy is an established and frequently performed surgical procedure in wrist surgery. The technical aspects of the procedure have continued to develop in recent years, with instruments and implants being developed specifically for this purpose. Ulnar shortening osteotomy is required for different clinical indications and situations. These varying indications demand different amounts of shortening, but all must be precise and accurate. Controversy exists as to how this can best be achieved in terms of the location for osteotomy, the surgical approach and geometry of the osteotomy, as well as which implant to use to provide optimal stability. The goal of all techniques (besides successfully resolving the underlying problem) is to achieve reliable and rapid bone union without compromising early functional rehabilitation and also to avoid hardware complications. The AO Hand Expert Group has developed a specialized instrumentation system with dedicated and specifically designed implants to ensure exact and accurate cutting with precise and rigid stabilization of the ulna. The matched drill guides and double-blade saws allow accurate completion of the planned amount of shortening together with precise coaptation of the osteotomy fragments. The specific ulnar osteotomy LCP (locking compression plate) combines maximum stability with minimum bulk and soft tissue irritation. The features of the implant, its surgical technique, and early results are described.
Keywords: ulnar shortening; osteotomy; ulnocarpal impaction